Analisis Efektivitas Fan Coil Unit Terhadap Pendinginan Area Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Kurniawanto, Hari; Inten Suwono, Niedya; Putri, Anatasya Delpia; Perangin Angin, Davin Gustio; Lanang Jati, Ignasius Prabadhatu; Juwita, Salsabila (Program Studi Teknik Mekanikal Bandar Udara, 2023)
Jendral Ahmad Yani International Airport Semarang has many scheduled flights, but there are some problems with the Fan Coil Unit. One of them is the wrong temperature when sent to a certain point in the room, which disturbs user comfort. The absence of Air Curtain and Window film in the area causes the temperature in the room to not meet capacity, especially in the check-in area of ​​Jenderal Ahmad Yani International Airport, Semarang. The results of this study can make the FCU work better and achieve the desired level of temperature accuracy by adding heat-reducing media such as air curtains, film, downlights, roof insulators which can maximize efficiency and channel temperature of the room considering that the Fan Coil Unit is one of the cooling aids which is quite important and always operates at the airport